2021
DOI: 10.1111/vde.12970
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of a hydrolysed fish and rice starch elimination diet for the diagnosis of adverse food reactions in cats: an open clinical trial

Abstract: Background -Diagnosis of adverse food reaction (AFR) is based on an eight week elimination diet (ED) and is confirmed by relapse upon re-challenge with the previously fed diet. Hydrolysed EDs are commonly used for this purpose.Objective -To evaluate the commercially available hydrolysed fish protein and rice starch ED Farmina UltraHypo (FUH) for the diagnosis of feline AFR.Animals -Thirty-two nonseasonally pruritic cats.Methods and materials -Pruritus was assessed with a new dual Visual Analog Scale, lesions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The prevalence of FA in this FAS colony was lower than the incidence reported previously in studies involving client‐owned cats 21–26 . According to a literature review, the prevalence of FA in cats with allergic skin disease is approximately 10% 27 .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…The prevalence of FA in this FAS colony was lower than the incidence reported previously in studies involving client‐owned cats 21–26 . According to a literature review, the prevalence of FA in cats with allergic skin disease is approximately 10% 27 .…”
Section: Discussionmentioning
confidence: 58%
“…The prevalence of FA in this FAS colony was lower than the incidence reported previously in studies involving client-owned cats. [21][22][23][24][25][26] According to a literature review, the prevalence of FA in cats with allergic skin disease is approximately 10%. 27 A recent study reported an adverse food reaction prevalence of 36% in cats fed with a hydrolysed diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations